PENGEMBANGAN MEDIA PEMBELAJARAN COOPERATION METHOD IN CANVA (COSMIC) PADA MATERI SISTEM TATA SURYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Herdiansyah, Dhean; Anna Maria Oktaviani; Sastra Wijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in elementary schools requires innovative instructional media to help students understand abstract concepts, particularly the Solar System topic. Based on a needs analysis conducted at SDN Kubang Apu, classroom instruction still relied on PowerPoint presentations, resulting in limited student engagement and difficulties in understanding the learning material. This study aimed to develop Cooperation Method in Canva (COSMIC) learning media and determine its feasibility and contribution to improving fifth-grade students' learning outcomes on the Solar System topic. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 35 fifth-grade students of SDN Kubang Apu, Serang City. Research instruments included expert validation sheets, teacher and student response questionnaires, interviews, observations, and pretest-posttest tests. The findings showed that the COSMIC media achieved feasibility percentages of 85.00% from the material expert, 91.25% from the media expert, and 96.25% from the language expert, indicating a very feasible category. Student responses reached 96.07%, while teacher responses reached 100%, both categorized as very good. Students' learning outcomes also improved, with the mean score increasing from 57.14 on the pretest to 76.00 on the posttest and an N-Gain score of 0.44 (moderate category). Therefore, the COSMIC learning media is feasible and practical to support science learning on the Solar System topic in elementary schools.